snoRNA, a novel precursor of microRNA in Giardia lamblia. - Ashesh A Saraiya (Public Library of Science (PLoS), 2008)
An Argonaute homolog and a functional Dicer have been identified in the ancient eukaryote Giardia lamblia, which apparently lacks the ability to perform RNA interference (RNAi). The Giardia Argonaute plays an essential role in growth and is capable of binding specifically to the m(7)G-cap, suggesting a potential involvement in microRNA (miRNA)-mediated translational repression. To test such a possibility, small RNAs were isolated from Giardia trophozoites, cloned, and sequenced. A 26-nucleotide (nt) small RNA (miR2) was identified as a product of Dicer-processed snoRNA GlsR17 and localized to the cytoplasm by fluorescence in situ hybridization, whereas GlsR17 was found primarily in the nucleolus of only one of the two nuclei in Giardia. Three other small RNAs were also identified as products of snoRNAs, suggesting that the latter could be novel precursors of miRNAs in Giardia. Putative miR2 target sites were identified at the 3'-untranslated regions (UTR) of 22 variant surface protein mRNAs using the miRanda program. In vivo expression of Renilla luciferase mRNA containing six identical miR2 target sites in the 3'-UTR was reduced by 40% when co-transfected with synthetic miR2, while the level of luciferase mRNA remained unaffected. Thus, miR2 likely affects translation but not mRNA stability. This repression, however, was not observed when Argonaute was knocked down in Giardia using a ribozyme-antisense RNA. Instead, an enhancement of luciferase expression was observed, suggesting a loss of endogenous miR2-mediated repression when this protein is depleted. Additionally, the level of miR2 was significantly reduced when Dicer was knocked down. In all, the evidence indicates the presence of a snoRNA-derived miRNA-mediated translational repression in Giardia.